2002
DOI: 10.1002/ijc.10381
|View full text |Cite
|
Sign up to set email alerts
|

High expression of tumor‐associated antigen RCAS1 in pancreatic ductal adenocarcinoma is an unfavorable prognostic marker

Abstract: RCAS1 (receptor-binding cancer antigen expressed on SiSo cells) is a recently identified human tumor-associated antigen expressed on various cancer cells. It is thought that tumor cells evade immune surveillance by expression of RCAS1, which induces apoptotic cell death in receptor-positive immune cells. The purpose of our study was to investigate the relation between RCAS1 expression and the clinicopathological variables and clinical outcome in patients with pancreatic adenocarcinoma. Immunohistochemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Using two-dimensional followed by mass spectrometry, autoantibodies against eIF-5A were detected in sera from patients having lung adenocarcinoma (45). RCAS1 is overexpressed in many cancers, such as uterine, breast, and pancreatic cancers (35,46,47). As indicated by the broad overexpression of RCAS1 in human cancers, some of the antigens we have identified may not be specific to ovarian cancer.…”
Section: Diagnostic Biomarkers In Ovarian Cancermentioning
confidence: 89%
“…Using two-dimensional followed by mass spectrometry, autoantibodies against eIF-5A were detected in sera from patients having lung adenocarcinoma (45). RCAS1 is overexpressed in many cancers, such as uterine, breast, and pancreatic cancers (35,46,47). As indicated by the broad overexpression of RCAS1 in human cancers, some of the antigens we have identified may not be specific to ovarian cancer.…”
Section: Diagnostic Biomarkers In Ovarian Cancermentioning
confidence: 89%
“…Expression of RCAS1 correlates with invasion or progression in several carcinomas (2,9,10). In addition, RCAS1 expression is associated with poor prognosis in uterine, lung, gallbladder, pancreas, and esophageal carcinoma (11)(12)(13)(14)(15). Although previous studies suggested that RCAS1 is also expressed in colorectal carcinoma cells, the relationship between RCAS1 expression and prognosis in colorectal carcinomas is not known at present.…”
mentioning
confidence: 99%
“…Cell surface staining with monoclonal antibody 22-1-1 and the presence of CD8 + T cells are both reported to be prognostic factors in a variety of cancers (9,10,12,23). In human colorectal cancer, the infiltration of CD8 + T cells into the cancer cell nest is a reliable positive prognostic indicator (21).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry revealed positive cell surface staining with 22-1-1 in a large number of different tumor tissues. In some tumor entities, 22-1-1 staining correlated with poor clinical prognosis (9,10). The physiologic molecular function of RCAS1 in humans, however, remains controversial.…”
mentioning
confidence: 99%